"Oh, Why Can't You Remain Like This Forever!": Children's Literature, Growth, and Disability - Teresa Michals; Claire McTiernan (Disability Studies Quarterly, 2018)
One of the foundational gestures of the disability rights movement was the rejection of the common description of people who live with physical or mental impairments as "eternal children." This paper argues that the contradictions inherent in applying this trope to adults amplify the contradictions inherent in applying it to children themselves. From its heyday in in the 19th-century "Golden Age" of children's literature to its afterlife in 20th-century disabling rhetoric, the fantasy of childhood as stasis requires denying the fact of growth.
Keywords: children' s literature; growth; romantic child; eternal child; disability; James Barrie; Harlan Ellison; Ashley X